The Effects of Task-oriented Mirror Therapy on the Upper Extremity Function and Brain Activation in Chronic Stroke Patients. (Medico Legal Update, 2020)
Background/Objectives: This study was conducted to examine how task-oriented mirror therapy changes the upper extremity function and brain activation in chronic stroke patients.Method/Statistical Analysis: This study applied mirror therapy to two stroke patients and used a paired t-test to examine the differences before and after treatment and the Telescan program to examine the brain activation.Findings: As a result of examining the upper extremity function after mirror therapy, the Fugl-Meyer Assessment scores improved from 21.0±1.41 before treatment to 24.5±1.71 after treatment, and the Wolf Motor Function test scores also improved from 27.0±5.66 to 33.5±6.36. The brain activity also increased after treatment.Improvements/Applications: The use of mirror therapy in stroke patients improved the recovery of upper extremity function and increased the brain activation.